PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN MENGGUNAKAN METODE PICTORIAL RIDDLE TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA SMA PADA MATERI ALAT ALAT OPTIK - Riscy Dewi Ramadani; Trapsilo Prihandono; Bambang Supriadi (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2021)
This research was conducted in SMAN Pakusari with the aim of knowing the effect of the guided inquiry learning model with the pictorial riddle method on learning activities and learning outcomes of high school students on the material of optical tools. The population used was all class XI in SMAN Pakusari and the selected sample are a class of XI IPA 2 and XI IPA 5 by using purposive sampling method. This research used pretest- posttest control group design . Data collection methods used in this research is a method of documentation, observation, and tests. The data collection instruments used were in the form of observation sheets to assess student learning activities and multiple choice tests to assess student learning outcomes. The results of the data analysis using the independent sample t-test showed the value of Sig. 2-tailed less than 0.05 (0,000 < 0.05) on student learning activity data and the independent sample t-test on learning outcomes shows sig 2.Tailed> 0.05 (0.159 > 0.05) on student learning outcomes data. Based on the data analysis, it can be concluded that the guided inquiry model with the pictorial riddle method has a significant effect on the learning activities and learning outcomes of high school students.